KONSEP DAN IMPLEMENTASI ETIKA ISLAM DALAM DUNIA BISNIS - Nurul Fatma Hasan (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2017)
The innovation of Islamic Bank’s products is an indicator of the ability of Islamic bank to adapt with the needs of modern human being. Basically, Islamic bank has been done some of innovation efforts, one of the effort is by engineering akad in fiqh muamalah. Some of akadin fiqh muamalah are not only adopted, but also adapted by Islamic bank so that in line with the people needs. The Islamic principal of freedom is the main capital of facing the complexity of economic problems and the highdemands of people in case of the role of Islamic bank. Hybrid contract (al-’uqud al-murakkabah) is an example of Islamic Bank strategy to develop bussiness innovation. Hybrid contract is a dealing of two parties to have muamalah that covers two or more akad. Hybrid contract has been used in many varians of Islamic bank’s products. For example IMBT, property financing (MMQ), syariah card, take over financing, Islamic pledge, current account product, Islamic checking account financing, Islamic bonds, and Islamic hedging.